From face-to-face to screen-to-screen instruction: Pakistani students’ experiences, challenges, and learning effectiveness - Ch. Mahmood Anwar; Aerni Isa (UIN Raden Mas Said Surakarta, 2022)
The closure of schools and campuses due to the COVID-19 pandemic in the recent years has been shocking and resulted in a new learning habit from face-to-face interaction to online activities. Challenges, problems, potentials, and other attributes related to the administration of online teaching and learning are highly necessary to be explored. This study is conducted to portray college students’ learning experiences at the time of COVID-19 pandemic as well as post-pandemic recovery in Pakistan. A narrative inquiry by means of written reflection and semi-structured interviews is employed to scrutinize the online learning experiences of 19 university learners’ studying at a medical university in Pakistan. This study’s results depict that the use social media has dominated the whole learning activities in higher education context experienced by the students. Although the students confessed that they were ill-prepared, and there were issues with electricity supply, unstable internet connection, and access to digital equipment, they were still motivated to engage in online learning activities. When they were asked to provide opinion about the teaching modes, most of them argued that face-to-face interaction in a formal classroom was more preferred. The findings offer an empirical implication that teachers and related stakeholders are required to enhance the efficacy of online learning activities in Pakistan. Moreover, the findings contribute as an input enhancement to improve the quality of digital learning from the students’ point of views, both at the time of COVID-19 pandemic and post-pandemic recovery.